Association between Respiratory Commorbidity and Covid-19 Mortality in Pasir Jaya Village, Cikupa District - hafizhah zaihan zulkarnain; Lilian Batubara (Junior Medical Journal, 2023)
Introduction : The COVID-19 pandemic in Indonesia started in March 2020 and there continues to be a constant increase in the number of cases and deaths due to COVID-19. Comorbid comorbidities (illnesses) experienced by patients at the start of treatment can increase the risk of death due to COVID-19 infection. Various foreign studies have shown that an elderly population with comorbidities has a higher risk of mortality compared to a population without comorbid diseases. Based on a study conducted on the link between lower respiratory tract comorbidities and mortality, the authors wanted to know the relationship between lower respiratory tract comorbidities and mortality in Pasir Jaya village, Cikupa district, Tangerang district.Method : This type of research is a descriptive observational study using a cross-sectional method. The sample in this study were 36 respondents who were COVID-19 patients in Pasir Jaya Village who had experienced COVID-19. Data was collected by conducting direct interviews with respondents. Bivariate analysis was performed using the Chi-Square statistical test.Result : : From the results of the analysis conducted, there were 88.9% of respondents who had comorbid respiratory tract died, 11.1% of respondents who had comorbid respiratory tract improved without symptoms, 11.1% of respondents who did not have comorbid lower respiratory tract improved with symptoms and 88.9% of respondents who did not have comorbidities improved without symptoms. on the chi-square test there is a value of 0.00. The results of the Chi-Square test obtained a p-value of 0.00 (0.05), thus it can be interpreted that there is a relationship between respiratory comorbidities and COVID-19 mortality.Conclusion : There is significant association between respiratory comorbidities and COVID-19 mortality.